Dependence of the size of titanium nitride particles and their agglomeration properties from parameters plasmodynamic synthesis - Sivkov A. A. Aleksandr Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Evdokimov A. A. Andrey Anatolievich; Usikov A. I. (2012, 2012)
Title screen.